Teenagers Tell Better Stories After Improvisational Theater Courses - Blonde, Manon; Mortelier, Frédérique; Bourdin, Béatrice; Hainselin, Mathieu (Frontiers in Psychology, 2021)
Improvisational theater (improv) is a booming theatrical practice, applying in many fields (teaching, medicine or entrepreneurship). Its effects on cognitive and behavioral processes are beginning to be demonstrated, despite scientific publications that are still rare, particularly about language. This study aimed to evaluate the effects of improv on adolescent narrative skills. Twenty-seven middle school students were recruited and divided into two groups: an IMPRO group (n = 13), composed of novice and intermediate improvisers, and a CONTROL group (n = 14), composed of middle school students doing theater. The evaluation took place in two experimental times spaces 3 months apart (11 sessions). It consisted in the creation of a written narrative resulting from previously observed images. We used quantitative criteria to carry out the analysis of this story (coherence, cohesion, lexicon, and syntax), according to the methodologies of PELEA and EVALEO. We showed an effect of the improv on coherence, which suggests that the practice of improv introduces teenagers to improve the narrative skills and the planification of a story, unlike written theater.